Echocardiographic but not clinical response to CRT is an independent predictor of a better survival free from arrhythmic events. (24th May 2021) - Valbom Mesquita, D; Parreira, L; Esteves, A; Farinha, J; Marinheiro, R; Amador, P; Fonseca, M; Lopes, C; Chambel, D; Goncalves, A; Caria, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiac resynchronization therapy (CRT) is of proven benefit in heart failure patients, improving mortality and reducing hospital admissions. There is however uncertainty if the arrhythmic risk is reduced in responders. Purpose: We aimed to assess if patients with a CRT implanted for primary prevention had less arrhythmic episodes if they responded to this therapy and if echocardiographic and clinical responses to CRT differ regarding the occurrence of ventricular arrhythmias. Methods: We prospectively enrolled patients that underwent CRT implant for primary prevention according to ESC guidelines. Patients were classified as responders if they fulfilled one of four criteria (echocardiographic or clinical) at six months after implant: a 5% absolute improvement in LV ejection fraction (LVEF), a 15% improvement in LVEF, a 15% decrease in LV end-diastolic volume or a decrease in NYHA class. During follow-up with device interrogation, arrhythmic ventricular events (AVE) were classified as appropriate ICD therapies or sustained ventricular tachycardia either occurring in ICD monitoring zones or undetected by the device due to a slower rare, but clinically documented. All patients were further classified according to type of pacing, biventricular or LV only. Demographic characteristics of patients were also assessed. Results: We enrolled 73 patients, 58 (79.5%) male, median age of 72 (65-77) years. Median LVEF was 28 (22-35) % (p = 0.95 between groups), ischemic etiology in 36 (46.6%, p = 1.00). The two groups with and without AVE did not differ significantly regarding clinical, echocardiographic, and electrocardiographic characteristics (table). CRT echocardiographic response criteria were met by 50 (68.5%) of patients and clinical criteria by 53 (72.6%) patients. AVE occurred in 15 (20.5%) patients. In univariate regression analysis, echocardiographic response was associated with reduced AVE (OR 0, 14; p = 0, 005). Clinical response to CRT was not associated with AVE (p = 0.07). LV only pacing was associated with a higher probability of AVE (OR 5.1; p = 0.038). In Cox regression multivariate analysis, response to CRT was the only independent predictor of better survival free from AVE (HR 0.28;CI 95%, p = 0.044) and LV only pacing was not associated with more episodes of ventricular arrhythmias (p = 0.17). Conclusions: Echocardiographic, but not clinical response to CRT therapy, is the only independent predictor of a higher survival free from arrhythmic events. In spite controversies regarding the arrhythmogenic role of LV pacing, this was not associated with higher ventricular arrhythmic events.